2011
DOI: 10.1016/j.indcrop.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of irrigated spring canola oil production to the US High Plains

Abstract: Canola oil is high in oleic acid which is commonly used for food and industrial purposes. To determine adaptability of spring canola (Brassica napus L.) to the High Plains for industrial oil production, 26 irrigated trials were conducted from 2005 to 2008. Trials were divided into five regions-1: 36-37 • N 108 • W; 2: 39-40 • N 101-103 • W; 3: 41-42 • N 102-103 • W; 4: 41-42 • N 104 • W; 5: 43-44 • N 106-108 • W. Cultural practices were based on site-specific protocols. Four cultivars, Hyola 401, Hyola 357 Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
3
29
1
2
Order By: Relevance
“…However, concentration of linoleic acid (20.5%) reported in the present study was higher. On the other hand, linoleic acid conent in camelina oil in the present study was nearly equal to that described in other studies [8]. Such variations in fatty acid content in camelina oil may be explained by the fact that besides cultivar specific characteristics, environmental conditions also affect fatty acid composition [2,7].…”
Section: Seed Oil Content and Fatty Acid Compositionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, concentration of linoleic acid (20.5%) reported in the present study was higher. On the other hand, linoleic acid conent in camelina oil in the present study was nearly equal to that described in other studies [8]. Such variations in fatty acid content in camelina oil may be explained by the fact that besides cultivar specific characteristics, environmental conditions also affect fatty acid composition [2,7].…”
Section: Seed Oil Content and Fatty Acid Compositionsupporting
confidence: 68%
“…Such a high economic value of camelina meal has tremendous potential in ensuring camelina biodiesel economically more viable. Growing environments influence quality and quantity of seed and oil yield of oilseed crops [8]. therefore it is important to develop regionspecific production technologies for a newly introduced crop in a particular agro-climatic region.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature during seed development is generally considered to account for most of the variations in fatty acid composition (Baux et al, 2008). Other important factors are solar radiation (Izquierdo et al, 2009) and water stress (Pavlista et al, 2011).…”
mentioning
confidence: 99%
“…However, the positive effects on seed production and quality may vary between cultivars and plantation sites, as differences in the number of seeds per silique and seed weight were found between the study sites (see Figures 1 to 6). Pavlista et al (2011) also observed differences in silique productivity and quality between production regions. For the cultivars studied, it is concluded that the cultivar Hyola 61 is more dependent on insect pollination than Hyola 420.…”
Section: Discussionmentioning
confidence: 80%